2022
DOI: 10.1038/s41746-022-00675-w
|View full text |Cite
|
Sign up to set email alerts
|

Automatic identification of tinnitus malingering based on overt and covert behavioral responses during psychoacoustic testing

Abstract: Tinnitus, or ringing in the ears, is a prevalent condition that imposes a substantial health and financial burden on the patient and to society. The diagnosis of tinnitus, like pain, relies on patient self-report, which can complicate the distinction between actual and fraudulent claims. Here, we combined tablet-based self-directed hearing assessments with neural network classifiers to automatically differentiate participants with tinnitus (N = 24) from a malingering cohort, who were instructed to feign an ima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A major goal for research on sensory disorders is to identify and refine a set of objective measurements – akin to what tumor imaging and biopsy data provide for oncologists or EEG measures of epileptiform activity provide to neurologists – that inform future care providers about the subtype and severity of the sensory disorder, the likelihood to benefit from a particular treatment, or whether they have demonstrated an improvement subsequent to treatment. While some measurements have been developed to identify whether an individual has tinnitus, they are insensitive to severity and lifestyle burden 39,58,59 . Here, we found that pupil dilation and facial reactions both demonstrated a correlation with symptom severity, though it was not clear whether these measures were redundant, nor how accurately they could predict an individual’s self-reported severity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A major goal for research on sensory disorders is to identify and refine a set of objective measurements – akin to what tumor imaging and biopsy data provide for oncologists or EEG measures of epileptiform activity provide to neurologists – that inform future care providers about the subtype and severity of the sensory disorder, the likelihood to benefit from a particular treatment, or whether they have demonstrated an improvement subsequent to treatment. While some measurements have been developed to identify whether an individual has tinnitus, they are insensitive to severity and lifestyle burden 39,58,59 . Here, we found that pupil dilation and facial reactions both demonstrated a correlation with symptom severity, though it was not clear whether these measures were redundant, nor how accurately they could predict an individual’s self-reported severity.…”
Section: Resultsmentioning
confidence: 99%
“…There are no objective measurements for the severity of tinnitus and sound sensitivity disorders. Instead, assessments rely on subjective self-report questionnaires, which can introduce vulnerabilities for malingering and false disability claims 39 and offer less insight into the underlying causes and potential treatments. Here, we hypothesized that involuntary autonomic and behavioral responses may have untapped potential as non-invasive, objective markers of tinnitus and sound sensitivity severity that are relatively easily to implement in laboratory and clinical settings.…”
Section: Introductionmentioning
confidence: 99%